1971
DOI: 10.1002/ijch.197100023
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Iodine and Bromine by Polyethylene Sulfide Containing Cotton Fabric

Abstract: The adsorption of iodine and bromine by polyethylene sulfide‐containing fabrics was investigated. It was found that the halogens could be adsorbed from aqueous solution as well as from a saturated halogen atmosphere. Adsorption was attributed to complexation by the sulfide bonds in the polymer. Adsorption from aqueous solution led to the formation of a complex with a molar ratio of halogen molecules (X2) to ethylene sulfide units of 1:1, while that from gaseous iodine a ratio of 2 was obtained. Complexation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1971
1971
1973
1973

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…With PES, the increase was over the whole range, but with PPS at 76°, an unexpected decrease in weight of the fabric was found. This may be due to cleavage of the sulfide linkages which are known to be less stable than PES bonds [8]. In fact, it was reported that mercuric chloride cleaved triphenylmethyl aryl sulfides to produce mercury aryl mercaptides [9] .…”
Section: Determination Of the Standard Heat Of Mercuric Chloride Adsomentioning
confidence: 99%
“…With PES, the increase was over the whole range, but with PPS at 76°, an unexpected decrease in weight of the fabric was found. This may be due to cleavage of the sulfide linkages which are known to be less stable than PES bonds [8]. In fact, it was reported that mercuric chloride cleaved triphenylmethyl aryl sulfides to produce mercury aryl mercaptides [9] .…”
Section: Determination Of the Standard Heat Of Mercuric Chloride Adsomentioning
confidence: 99%
“…It was shown [5] that polypropylene sulfide grafted on cellulose membrane adsorbed silver nitrate from aqueous solutions. In a previous paper [6] the preparation of high polyethylene sulfide-containing fabrics was described. The polyethylene sulfide was either present as a 9 70 AVNY, GUR-ARIEH, AND ZILKHA graft polymer or as a homopolymer which was formed inside the fabric.…”
Section: Introductionmentioning
confidence: 99%
“…EXPERIhf ENTAL Cotton fabrics of high polyethylene sulfide content were prepared as previously described [6] . Homopolyethylene sulfide was obtained by polymerizing the monomer with lithium methoxide.…”
Section: Introductionmentioning
confidence: 99%